La argumentación en el aula. Revisión documental de publicaciones de 1994 a 2019. (2020)
In this compilation monograph a bibliographic analysis is established about the teaching processes of argumentation in the school context, taking as a reference for its development various investigations and studies (academic reflections) carried out during the period from 1994 to 2018. In the text a review is proposed, as an analysis, in which it looks to understand the progress that has been made in the teaching of argumentation in school, its importance and its use in education. In this way, the main perspectives and approaches that prevail in academic fields in relation with argumentation, this was achieved thanks to the identification of seven specific categories, which are, teaching of argumentation, evaluation of argumentation, scientific argumentation, instrumentalization, argumentation in context, theoretical references and learning difficulties, these allowed to divide the fifty corpus analyzed and Thus, understanding and inferring reflections and opportunities for improvement in the processes of argumentative teaching in the school context.